Interpreting the differences in microbial carbon and nitrogen use efficiencies estimated by 18O labeling and ecoenzyme stoichiometry - Sun, Lifei; Qu, Lingrui; Moorhead, Daryl L.; Cui, Yongxing; Wanek, Wolfgang; Li, Shuailin; Sang, Changpeng; Wang, Chao (Geoderma, 2024)
•Microbial CUE and NUE estimated by the 18O-approach were negatively related to those estimated by the enzyme model using C:P stoichiometry.•Microbial CUE and NUE estimated by the 18O-approach and enzyme model using C:P stoichiometry showed opposite responses to pH, MAP, and AP.•Microbial CUE and NUE estimated by both the 18O-approach and enzyme model using C:P stoichiometry showed a positive relationship under the condition of P limitation. Microbial carbon and nitrogen use efficiencies (CUE and NUE) are central to our understanding of soil C and N cycling. Although both the 18O-labeling approach and ecoenzyme stoichiometry model have been widely used to estimate microbial CUE and NUE, comparisons of the two methods are scarce. Here, we investigated soil microbial CUE and NUE of 11 locations along a forest transect in eastern China using both the 18O-approach and ecoenzyme model. We found that microbial CUE-18O and NUE-18O estimated by the 18O-approach were positively related to each other and both decreased with soil acidification and phosphorus acquisition as measured by enzyme activity. However, CUEC:N and NUEN:C, estimated by C:N stoichiometry using the enzyme model were negatively related to each other and neither showed any relationship to soil acidification or phosphorus acquisition. Finally, CUEC:P and NUEN:P estimated according to C:P stoichiometry were positively related to each other and both increased with soil acidification and phosphorus acquisition efforts. We suggest that a reason for these differences is that the 18O-approach reflects the intracellular biochemical transformation of C, N, and P while the enzyme models reflect stoichiometric imbalances between external substrates and microbial biomass, i.e., different aspects of microbial metabolism. Moreover, differences between the C:N and C:P-based enzyme models resulted from P-limitation to soil microorganisms in this system. For these reasons, microbial element use efficiencies need to be clearly defined, i.e., as derived from growth-based or soil enzyme-based measurements, and caution must be made when comparing results obtained from different methods, and under different conditions of resource availability.